Sensitive detection of intracellular RNA of human telomerase by using graphene oxide as a carrier to deliver the assembly element of hybridization chain reaction. Issue 9 (31st March 2016) - Shi, Zhilu; Zhang, Xiafei; Cheng, Rui; Li, Baoxin; Jin, Yan
Abstract : An enzyme-free amplification strategy has been developed for sensitively and specifically detecting intracellular RNA of telomerase via GO-aided hybridization chain reaction (HCR). Abstract : Since the level of human telomerase RNA (hTR) in tumor cells is higher than that in normal somatic cells, the quantitative assay of hTR is of significant importance in tumor diagnosis. Herein, graphene oxide (GO) was simultaneously exploited as a fluorescence quencher and a carrier of nucleic acid to successfully deliver two hairpin DNA probes of hybridization chain reaction (HCR) into the cancer cell for detecting telomerase RNA based on DNA nanoassembly of HCR. The sticky end of HCR probes could tightly absorb on the surface of GO, resulting in fluorescence quenching of the dye which was tagged at the sticky end of two hairpin probes. When faced with hTR, the fluorescence of DNA probes is subsequently recovered because hTR could trigger HCR to autonomous assembly of a DNA polymer which released from the GO and led to fluorescence recovery. Taking advantage of nucleic acid nanoassembly of HCR, this intracellular HCR strategy creates enormous signal amplification, and enables ultra-sensitive fluorescence imaging of hTR expression. By monitoring fluorescence change, human telomerase RNA could be specifically studied and this method can also be used for detecting single-base mutation. The GO-aided HCR strategy allowed us to sensitively detect hTR in a living cell, which holds great potential for analyzing other low-abundance biomolecules in living cells via HCR.